2023
DOI: 10.3389/fcvm.2023.1215397
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of two competitive devices for retrograde closure of perimembranous ventricular septal defects

Abstract: BackgroundRetrograde closure of perimembranous ventricular septal defects (pmVSDs) is a well-established procedure. However, interventionists are still looking for the best closure device.MethodsWe performed a single-center retrospective review of 5-year-experience (from July 2015 to July 2020) with retrograde closure of pmVSDs using AmplatzerTM Duct Occluder II (ADOII) and KONAR-MF™ VSD occluder (MFO). Deficient sub-aortic rim (SAR) (≤2.5 mm for MFO and ≤3 mm for ADOII) was an exclusion criterion in defects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In cases where an ADOII device is used to prevent the development of AR and ensure a safe zone, it is recommended to have a SAR of ≥3 mm ( 20 ). In our study, we excluded defects with deficient SAR, even though it has been reported as feasible by other operators ( 31 ). The attachment point of the MFO device is flexible, allowing for the placement of the RV and LV discs at different angles.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where an ADOII device is used to prevent the development of AR and ensure a safe zone, it is recommended to have a SAR of ≥3 mm ( 20 ). In our study, we excluded defects with deficient SAR, even though it has been reported as feasible by other operators ( 31 ). The attachment point of the MFO device is flexible, allowing for the placement of the RV and LV discs at different angles.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the plug softness and its design on the left side, the occluder fits very well within the aneurysm reducing the risk of residual shunt. It also seems really appropriate in cases of multiple exits on the right side or multifenestrated defects including the Gerbode-type VSD [1,[3][4][5][6][7][8][9][10], which is not a limitation although only one exit is crossed by the device. In this setting, to obtain full occlusion was more complex but possible, and this was noticed in half of our patients, even if two patients received a second occluder, as already reported [9].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, both the whole plug on the left side covering the LV entry and the retention disk on the right side could achieve full occlusion of the defect. Haddad has suggested that device undersizing may be associated with a persistent shunt in patients with a multifenestrated defect and should be avoided [3,10]. In addition, the possibility of connecting the device to the delivery cable from either the left or the right side is also a real advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Not all cases used eccentric occluders, as symmetrically concentric VSD occluder could close the infundibular or aneurysmal structure without affecting the aortic valve. Despite previous encouraging results by other operators using mixed guidance, VSD closure was avoided in cases without an aneurysmal structure and when the subaortic rim was less than 1 mm (25).…”
Section: Complicationsmentioning
confidence: 97%